Nec‐1 alleviates cognitive impairment with reduction of Aβ and tau abnormalities in APP/PS1 mice - Seung‐Hoon Yang; Dongkeun Kenneth Lee; Jisu Shin; Sejin Lee; Seungyeop Baek; Jiyoon Kim; Hoyong Jung; Jung‐Mi Hah; YoungSoo Kim (EMBO Molecular Medicine)
Abstract Alzheimer's disease (AD) is a neurodegenerative disorder characterized by cognitive symptoms of learning and memory deficits. Such cognitive impairments are attributed to brain atrophy resulting from progressive neuronal and synaptic loss; therefore, alleviation of neural cell death is as an important target of treatment as other classical hallmarks of AD, such as aggregation of amyloid‐β (Aβ) and hyperphosphorylation of tau. Here, we found that an anti‐necroptotic molecule necrostatin‐1 (Nec‐1) directly targets Aβ and tau proteins, alleviates brain cell death and ameliorates cognitive impairment in AD models. In the cortex and hippocampus of APP/PS1 double‐transgenic mice, Nec‐1 treatment reduced the levels of Aβ oligomers, plaques and hyperphosphorylated tau without affecting production of Aβ, while it altered the levels of apoptotic marker proteins. Our results showing multiple beneficial modes of action of Nec‐1 against AD provide evidence that Nec‐1 may serve an important role in the development of preventive approach for AD.